The burden of proof for the unseizability of small rural property in light of jurisprudential interpretation: An Analysis of STJ Special Resource Number 1913234 Regarding the Divergence in Proving Family Exploitation of Small Rural Property - Cavalcante, Italo Ricardo Lopes; Oliveira, Rômulo de Morais e (JRG Journal of Academic Studies, 2024)
Considering studies on property rights, which span various contexts, including the fulfillment of its social function as guaranteed by the Federal Constitution, this paper aims to examine the doctrinal and jurisprudential understanding of the burden of proof concerning the unseizability of small rural properties. The research method employed involved theoretical publications, legal norms, doctrines, jurisprudence, laws, and bibliographic sources, including websites. The deductive approach was used as the method of reasoning, and the descriptive-analytical method was applied for procedural analysis. Which allows us to conclude that, despite the Superior Court of Justice's established thesis, legislative gaps result in continued uncertainty regarding the protection of rural property owners in vulnerable situations.